The Coal Dust Combustion Scheme for an Invert Furnace of an A-USC M-Shaped Boiler - Prokhorov V.B.; Kirichkov V.S.; Chernov S.L.; Fomenko N.E. (Problems of the Regional Energetics, 2022)
. The M-shaped boiler construction for the advanced ultrasupercritical steam parameters (A-USC) is proposed in this work. The boiler was designed to operate in a 500 MW unit on low volatile hard coal. This design allows reducing the pipelines length of the high cost steam pipelines made of nickel alloys. A downstream (invert) furnace is offered for this boiler type. The coal dust burning scheme design using the direct-flow burners and nozzles in a system of vertical and horizontal tangential torches and the solid ash removal are proposed. This approach was extensively used earlier on standard shaped boilers, and it was upgraded now for an invert furnace. The goals are achieved by conducting research on the physical furnace model and thermal furnace processes numerical simulation by computational fluid dynamics software. The most significant research results were as follows: the oxidizer stage supply was performed along the torch length and furnace height; the dynamic jet pressure on the furnace walls was excluded; a high degree of coal burnout was ensured due to the vortex furnace aerodynamics implementation; the uniform furnace section filling with air jets was performed; turbulent jets ejection was significantly higher than that for a flat submerged jet; chemical underburning loss did not exceed 0.1%; and unburned carbon loss was 0.8%. The carbon monoxide concentration at the furnace outlet in terms of air excess ratio equal to α=1.4 was 226 mg/nm3. The nitrogen oxides concentration in the flue gases (normalized) was 424 mg/nm3. The results significance obtained during the research is efficient solid fuel use with high technical and economic boiler performance.